Prospective study of formalin‐fixed Mohs surgery and haematoxylin and eosin stains with control contralateral biopsies for lentigo maligna: 5‐year follow‐up results. (1st August 2014) - Lawrence, C.M.; Rahim, R.; Charlton, F.; Husain, A.
Summary: Background: There is little consensus on the optimum form of surgical management for lentigo maligna (LM). Currently, because malignant melanocytes spread down adnexal structures, full‐thickness skin removal is the only surgical option. Interpretation of Mohs histological specimens is difficult because of the presence of abnormal melanocytes in otherwise normal sun‐damaged skin. Objectives: To investigate Slow Mohs for surgical excision of LM, to see whether the use of control contralateral skin biopsies would enable the end point of excision to be more easily interpreted and to investigate factors that influence the subclinical amelanotic extensions of LM. Methods: The Slow Mohs technique for formalin‐fixed tissue was used in 74 patients with LM. Before surgery LMs were classified as well defined, poorly defined, incompletely excised or recurrent. Control biopsies were taken from healthy skin of the contralateral side. Specimens were processed in formalin, stained with haematoxylin and eosin (H&E) and the results read at 24–48 h. The excision margin required for complete excision was measured and patients were followed for a minimum of 5 years to exclude recurrence. Results: On average the final excision margin required was 6·7 mm. Margins were significantly greater for ill‐defined, recurrent and incompletely excised LM compared with well‐defined LM. The presence of depigmented patches preoperatively did not correlate with the excision margin, but LMs showing nesting required significantly wider excision margins. There were seven (12%) recurrences at a mean 4·4 years after surgery in the group with 5‐year follow‐up. Recurrence occurred only in recurrent and ill‐defined primary LM. Conclusions: The use of Slow Mohs formalin‐fixed tissue and H&E section staining, even with comparator biopsies, does not provide sufficient discrimination to identify residual disease confidently.